Real-time pulp temperature change at different tooth sites during fabrication of temporary resin crowns - Maykon Dias; Joanne Jung Eun Choi; Caira Ellyse Uy; Rishi Sanjay Ramani; Ritu Ganjigatti; John Neil Waddell (Heliyon, 2019)
Aim: To record the pulp temperature at different tooth sites during fabrication of two different temporary crown systems. Methodology: Two temporary crown systems were investigated; a conventional direct fabricated and a preformed thermoplastic resin system. Extracted caries-free human teeth (incisor, premolar and molar) were prepared for full coverage ceramic restoration with roots sectioned below the cemento-enamel junction. Thermocouple wires were secured at the surface of crown material, the cut dentine and inside the pulp cavity. Provisional crowns (n = 10/group) from each system were formed prior to placement in a water bath of 37 °C to simulate pulpal temperature. Temperatures were recorded using a K-type thermocouple data logger to collect the mean and peak temperature during crown fabrication. Statistical analysis was carried out on all tested groups and heat flow was calculated. Results: For direct fabricated crowns, the mean rise in pulpal temperature recorded was 0.1 °C with the mean temperature range of 37.3 °C–37.8 °C. For the preformed thermoplastic crowns, the mean rise in pulpal temperature recorded was 37.3 °C–45.1 °C. The increase in temperature was significantly higher (6.5 °C for the incisor group, 7.5 °C for the premolar group, and 6.7 °C for the molar group). For both crown systems, the temperature difference between the three different sites; pulp, crown and tooth surface showed a statistical difference (P < 0.01). Conclusions: The direct fabrication system showed minimal temperature changes within the teeth, while the preformed thermoplastic fabrication system showed larger temperature change in the teeth.